Minimally invasive distal metaphyseal metatarsal osteotomy (DMMO) for symptomatic forefoot pathology – Short to medium term outcomes from a retrospective case series. (March 2019) - Malhotra, Karan; Joji, Nikita; Mordecai, Simon; Rudge, Ben
Highlights: DMMOs may be used to treat metatarsalgia caused by relatively long metatarsals. The mean shortening achieved with DMMOs in this series was 3–4 mm per metatarsal. This degree of shortening was sufficient to alleviate symptoms in majority of cases. DMMOs can produce excellent radiological and clinical outcomes in the medium term. DMMOs of only the 2nd and 3rd rays may result in transfer metatarsalgia of the 4th. Abstract: Background: Minimally invasive distal metaphyseal metatarsal osteotomy (DMMO) may be used to treat metatarsalgia and forefoot pathology. Few large series report its results or examine the degree of metatarsal shortening with this technique. The clinical and radiographic results of a cohort of patients treated with DMMOs at our unit are reported. Methods: This was a single-centre retrospective study looking at the outcome of consecutive patients undergoing DMMOs. Demographics, radiological and clinical outcomes, complications and patient reported outcome measures (PROMs) were analysed. Results: DMMOs on 106 toes in 43 feet were included. Mean age was 60.2 ± 10.2 years and median follow-up was 38 months. Concurrent procedures were performed in 26 cases (60%). DMMO was performed on multiple toes in 42 cases (97%). Mean shortening achieved was 3.6 ± 2.2 mm, 4.1 ± 1.6 mm, and 3.6 ± 1.6 mm for the second, third and fourth metatarsals respectively. Mean time to fusion was 11.4 ± 7.8 weeks and union occurred in 105 toes (99%). The single non-union was asymptomatic at 12 months. Two patients required a subsequent additional DMMO for transfer metatarsalgia. Minor complications were seen in 11 patients (26%). At final follow-up PROMs data was available for 42 cases: mean MOxFQ was 28.8 ± 27.6, mean EQ-5D was 0.789 ± 0.225, mean EQ-VAS was 68.5 ± 20.3, mean VAS-Pain score was 3.1 ± 2.8, and patients were satisfied overall in 40 cases (95%). Conclusions: The authors demonstrate excellent radiological and clinical outcomes in the short to medium term with DMMOs and present data on metatarsal shortening achieved with this technique.